Mental Health from Al-Ghazali's Perspective - Nuriyyah, Habibatun; Achmad Khudori Soleh (Medina-te : Jurnal Studi Islam, 2026)
Al-Ghazali defines mental health as a harmony between mental and physical functions characterised by a person's ability to adapt to their environment. This theme is an important study because it reveals the concept of mental health from one of the Islamic figures, namely Al-Ghazali. The purpose of this study is to examine and explore the understanding related to mental psychology expressed by Al-Ghazali. The method used in this study is library research or literature study by utilising content analysis to identify patterns, themes or concepts contained in the content. The results of this study show several points, namely (1) The soul is defined by Al-Ghazali as a subtle and single spiritual substance that is not divided, or commonly called Al-Nafs. (2) Al-Ghazali categorises a healthy soul as one that can be characterised by a strong model of faith, freedom from heart disease, noble morals, good social relationships, and the achievement of happiness in this world and the hereafter. (3) Al-Ghazali also explains the efforts required to achieve peace and happiness in order to attain true mental health. These efforts can take the form of mujahadah or sincere efforts in the form of dhikr, worship and good deeds, riyadlah or spiritual training in the form of restraining lust and guarding the tongue, and also tazkiyatun nafs or purification of the soul which is divided into three stages, namely takhalli, tahalli, and tajalli.